Redefying the strength between CSR and sustainable social performance through mediational role of green intellectual capital - Muhammad Haroon Rehan; Sook Fern Yeo; Irfan Ullah Khan; Cheng Ling Tan (Cleaner and Responsible Consumption)
This study investigates the mediating role of Green Intellectual Capital (GIC) in the relationship between Corporate Social Responsibility (CSR) and Sustainable Social Performance within the context of Islamic banks in Pakistan. The population of interest comprises bank employees, including managers, operation managers, operations officers, and cash officers, from 15 Islamic banks operating 150 branches in the southern region of Khyber Pakhtunkhwa, Pakistan. The total population in these banks is 1600 employees. Using Yamani’s (1967) formula, a sample of 320 employees was selected. Non-probability sampling, involving non-random selection based on convenience, was employed to facilitate data collection. The methodology involves employing mediation analysis to explore the complex relationships among CSR, GIC, and Sustainable Social Performance. The analysis reveals a robust correlation between CSR and GIC (R = 0.866), with GIC significantly predicting CSR (Beta = 0.772, p < 0.001). Additionally, both CSR (Beta = 0.535, p < 0.001) and GIC (Beta = 0.327, p < 0.001) have significant positive impacts on Sustainable Social Performance. The study also confirms a direct positive effect of CSR on Sustainable Social Performance (B = 0.535, p < 0.001). The results indicate that GIC not only directly influences Sustainable Social Performance but also mediates the relationship between CSR and Sustainable Social Performance. This nuanced understanding contributes to the literature by highlighting the importance of GIC as a mediator in CSR initiatives aimed at enhancing social performance. The findings provide valuable insights for Islamic banks and similar financial institutions in developing countries, suggesting that integrating GIC into CSR strategies can significantly enhance Sustainable Social Performance. This research underscores the need for developing comprehensive CSR policies that incorporate GIC to foster sustainable practices and improve social outcomes among bank employees in Pakistan and other developing economies.